2017
DOI: 10.1063/1.4973555
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and theoretical study of an atmospheric air plasma-jet

Abstract: In this work, we present an experimental and theoretical study of a low frequency, atmospheric plasma-jet discharge in air. Voltage-current characteristics and spectroscopic data were experimentally obtained, and a theoretical model developed to gain information of different aspects of the discharge. The discharge is modeled as a cathode layer with different mechanisms of electron emission and a main discharge channel that includes the most important kinetic reactions and species. From the electric measurement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
16
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 22 publications
3
16
0
Order By: Relevance
“…This relatively low voltage is due to the high conductivity of the plasma channel that develops after a breakdown phase. The breakdown phase appears at the beginning of each half cycle when the applied voltage reaches values around 5 kV for INFIPjet and 2 kV for Magiplas and is observed in the electrical signals as current and voltage spikes (of about 100 μs duration) corresponding to micro‐arcs interrupted by the high inductance behavior of the power source before the more stable discharge is established . The shape modification of the rear electrode to a sharp needle intensifies the electric field on the central axis producing a decrease in the breakdown potential that can explain the reduction by about half in the number of spikes of Magiplas.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This relatively low voltage is due to the high conductivity of the plasma channel that develops after a breakdown phase. The breakdown phase appears at the beginning of each half cycle when the applied voltage reaches values around 5 kV for INFIPjet and 2 kV for Magiplas and is observed in the electrical signals as current and voltage spikes (of about 100 μs duration) corresponding to micro‐arcs interrupted by the high inductance behavior of the power source before the more stable discharge is established . The shape modification of the rear electrode to a sharp needle intensifies the electric field on the central axis producing a decrease in the breakdown potential that can explain the reduction by about half in the number of spikes of Magiplas.…”
Section: Resultsmentioning
confidence: 99%
“…It is based on an air discharge without dielectric barrier formed in a gap between plane perforated electrodes (1 mm central perforation) separated by 1 mm. The discharge has the characteristics of a contracted glow with a relatively high voltage cathode layer . Electrodes are assembled by a dielectric of PTFE with a 3 mm central perforation (Figure a).…”
Section: Methodsmentioning
confidence: 99%
“…Several kinetic schemes have been proposed in the literature for modelling atmospheric pressure nonequilibrium air discharges, such as streamers [1,2], low-current arc and glow discharges at rest (or in low gas flows) [3][4][5][6], glow discharges in fast gas flows [7][8][9], and high-current pulsed discharges [10][11][12][13][14][15]. It is found that the ionization by electron impact of O 2 and N 2 molecules dominates at low-gas temperature (T g is below the range of 1000-2000 K [10,14,15]), while the electron-impact ionization of NO molecules is written as: e + NO → NO + + e, (R3) (1) where R refers to the reactions used in the model.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, more efficient channels for associative ionization may appear [16]. However, despite the great interest and importance of ionization processes in hot air discharges, the influence of the electronically excited states of reactants on associative ionization processes is yet unclear, as they are not routinely considered in air kinetic models [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15]. To answer this question, it is necessary to carry out more comprehensive investigations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation